Safety and immunogenicity of inactivated COVID-19 vaccine in patients with metabolic syndrome: A cross-sectional observational study - Guo, Qiao; Yang, Lei; Peng, Ran; Gao, Tao; Chu, Xinglin; Jiang, Depeng; Ke, Dazhi; Ren, Hong (Frontiers in Public Health, 2022)
Results: In terms of safety, all AEs in 3H patients were mild and self-limiting, and the incidence was comparable to that of HC participants, with overall AEs within seven days reported in 9.6% (15/157) of 3H and 11.1% (13/117) of HC. Both groups experienced no serious adverse events. As for immunogenicity of 3H patients to inactivated COVID-19 vaccination, compared with health controls, the seroprevalence of anti-RBD IgG and CoV-2 Nab was significantly decreased in 3H patients ( p = 0.000, p = 0.003, respectively), while the titers of anti-RBD IgG (AU/ml) and CoV-2 Nab (µg/ml) were also significant lower in 3H patients (p = 0.014, p = 0.002, respectively). As for frequencies of B cells, 3H patients had lower frequencies of RBD-specific B cells, RBD+ resting MBCs, and RBD+ intermediate MBCs (p = 0.003, p = 0.000, p = 0.000, respectively), but had a higher frequencies of RBD+ atypical MBCs (p = 0.000) than HC. In comorbidity number subgroups analysis of 3H, except frequencies of RBD+ resting MBC cells, RBD+ activated MBC cells and RBD+ intermediate MBC cells had significant difference among three groups (p = 0.035, p = 0.042, p = 0.046, respectively), antibody response had no significant difference among 1H, 2H, and 3H groups (p > 0.05). And took 70 years old as a boundary, also no statistically significant differences (p > 0.05) were found in age subgroups. Lastly, comprehensive analysis in 3H patients indicated that interval time after 2nd dose vaccine was the statistical significant factor which impacting antibody response in 3H individuals. Conclusions: Inactivated COVID-19 vaccines were well tolerated, but induced a poorer antibody response against SARS-CoV-2 in 3H patients comparing to HC participants. Patients with 3H should therefore be more proactive in receiving inactivated COVID-19 vaccine, and a booster vaccination may be considered necessary.